Muslim di Prancis ‎(Dinamika, Eksistensi dan Historis)‎ - Maharani Suryadie Putri; Firdaus Imaduddin (Journal of Comparative Study of Religions (JCSR), 2021)
This study aims to reveal the phenomena, historical facts, and developments of Islamophobia in France from time to time and the government's attitude about it. The type of research is qualitative research, using historical methods. The data are collected from journals, newspapers, historical records and verbal reports. The results of this study indicate that there are changes in the reaction of the French authorities to Muslims. In 1914-1918 France accepted workers from Islamic countries. While between 1976 and 1989, massive places of worship were built, French Muslims also formed religious organizations and communities. However, several incidents of terrorism which occurred in various parts of the world that accuse Islam as the perpetrator behind it all, gave rise to the term 'Islamophobia' in the West. As a result, the French authorities made several regulations that clearly discriminated against Muslims. The issue of Islamophobia is based on at least three things; first, Islam has been considered an integral part of French society. Second, Islam is the cause of the economic recession. Third, the September 11 tragedy made Islam labeled as a terrorist actor.